CENTROID-MOMENT TENSOR SOLUTIONS FOR JULY-SEPTEMBER 1985 - Dziewonski, A; Franzen, J; Woodhouse, J (1986)
Centroid-moment tensor solutions are presented for 183 earthquakes that occurred during the third quarter of 1985. The solutions are obtained using corrections for aspherical Earth structure. © 1986.